Reviving Cultural Roots through Knowledge Management and Modern Media in Southern Thailand - Meena Raden Ahmad; Ganyarat Pinichchan; Paweena Jeharrong (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2026)
This article aims to elucidate the application of knowledge management in revitalizing cultural roots through modern media in Thailand's three southernmost border provinces. Specifically, it examines how knowledge management can facilitate the collection, transmission, and dissemination of cultural knowledge. The study employs a mixed-methods research design, incorporating focus group discussions, in-depth interviews, and satisfaction questionnaires. Qualitative informants comprised local scholars, community leaders, media content creators, producers, and communication academics, while quantitative data were collected from 400 residents across the three southern border provinces. The findings reveal that the knowledge management process, grounded in the SECI(Socialization, Externalization, Combination, Internalization) conceptual framework, enables the systematic conversion of tacit community knowledge into explicit knowledge. Evaluation results indicate that the developed media achieved a high level of overall satisfaction, with the dimension of utility and practical applicability yielding the highest mean score. The findings suggest that the integration of knowledge management with modern media effectively bridges local community knowledge to broader public audiences, thereby safeguarding cultural heritage from loss, enhancing knowledge accessibility among the general public and youth, and fostering participatory engagement in the preservation and transmission of cultural heritage within a contemporary social context.